Communicative event and its representation in discourses of various types (based on the languages of the Еuropean cultural area) - Radziievska , Tetiana (Current issues of Ukrainian linguistics: theory and practice, 2025)
The paper deals with the lexical and syntactic means of representing a communicative event in discourses of various types. The main focus of the paper is made on a fictional and media discourses. The subject of the study is syntactic structures, which consist of two components, the so-called direct speech and the accompanying words of the author (a remark). These components reflect speech with different subject-addressee coordinates, as a result of which, the structures that they consist of became heterogeneous from a linguosemiotic point of view. The illustrative material of the study covers Ukrainian, English, French, Italian, and German texts. Structures under consideration are interpreted as a linguocultural stereotype formed in the process of development of language and culture to represent a speech event. At the same time, the data of different languages diagnoses tangible variability of structures in their textual design. In some national traditions, there is a tendency to "bring together" two components of the syntactic structure through the use of punctuation marks, while in others, on the contrary, there is a tendency to segment them and make them autonomous. In fictional discourse numerous cases of simple and complex combinations are presented, with an initial, medial or final position of one of them. The lexical toolkit for representing a communicative event is aimed at reflecting the essential characteristics of speech and speech behavior of the communicant. There are verbs whose semantics contain information about the mode of speech action, as well as its intentional component. Lexical means that reflect the paralinguistic plan of speech, various gestures, movements, voice, tone are used intensively to describe additional psychological details and nuances of speech behavior. Texts of modern media discourse also demonstrate the use of these syntactic constructions and their variability. It is shown that their functional load in modern media texts is determined by the actualization in social space of information of a certain type and reader expectations. It is noted that structures under consideration are not typical for reference discourse (encyclopedias, reference books), legal discourse (codes), academic discourse, and are limitedly represented in discourses of other types.